2018
DOI: 10.1007/s00066-017-1258-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective feasibility analysis of a novel off-line approach for MR-guided radiotherapy

Abstract: This trial demonstrated for the first time the feasibility and patient compliance of a shuttle-based off-line approach to MRgRT of pelvic malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
1
21
1
Order By: Relevance
“…Magnetic resonance (MR) imaging, with its superior soft-tissue contrast, facilitates enhanced differentiation between cancerous and healthy tissue as well as functional assessment of treatment response [ 5 , 6 ]. Given the technical challenges in integrating MR imaging (MRI) into a linear accelerator, first studies on MR-guided radiotherapy (MRgRT) focused on offline solutions and reported efficacy and feasibility for this technique [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance (MR) imaging, with its superior soft-tissue contrast, facilitates enhanced differentiation between cancerous and healthy tissue as well as functional assessment of treatment response [ 5 , 6 ]. Given the technical challenges in integrating MR imaging (MRI) into a linear accelerator, first studies on MR-guided radiotherapy (MRgRT) focused on offline solutions and reported efficacy and feasibility for this technique [ 7 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dosimetric deviations in prostate radiotherapy resulting from intra- and interfractional anatomic variability have been incompletely understood, and an in-depth comprehension about the dosimetric impact of position verification imaging becomes more important as individual fraction dose are increasing for hypofractionated or even stereotactic treatment approaches ( 18 , 19 , 30 ). Previous analyses have generally been limited by the insufficient quality or frequency of position verification imaging and the lacking availability of elastic image registration tools.…”
Section: Discussionmentioning
confidence: 99%
“…Our manuscript analyzed data from a prospective trial investigating daily MRI in treatment position as a means of off-line MR-guided radiotherapy [19,20]. In this study, 8 patients with locally advanced rectal adenocarcinoma were enrolled between October 2013 and June 2017.…”
Section: Patientsmentioning
confidence: 99%
“…All patients received daily short MR scans in treatment position prior to irradiation with the same immobilization equipment used for RT to image the morphological and functional changes of the tumorous tissue during the treatment. The transfer of patients between the MR device and the linear accelerator was realized with a shuttle system (Zephyr system, Diacor, Salt Lake City, USA) [19].…”
Section: Patient Immobilization and Treatment Planningmentioning
confidence: 99%